(untitled) - Sommerville, Ian (New York, 2004)
Software Engineering presents a broad perspective on software systems engineering, concentrating on widely used techniques for developing large-scale systems. The objectives of this seventh edition are to include new material on iterative software development, component-based software engineering and system architectures, to emphasize that system dependability is not an add-on but should be considered at all stages of the software process, and not to increase the size of the book significantly.
Phân tích yêu cầu phần mềm
Keywords: Software engineering,Kỹ thuật phần mềm